Recurrent Interstitial Pregnancy: a Review of the Literature - Egger, Eva (Geburtshilfe und Frauenheilkunde, 2017)
Interstitial pregnancies account for 2–4 % of all ectopic pregnancies. Despite its rarity, various treatment options exist. However, no gold standard has yet been defined and data regarding recurrence of interstitial pregnancies in subsequent pregnancies after different treatments are sparse. This makes it very difficult to provide adequate patient counselling for treatment options with regards to the treatment-related risk of recurrence. The present literature review demonstrates that recurrent interstitial pregnancy is a rare condition and more likely when additional anatomy-related risk factors for ectopic pregnancies are present, such as hydrosalpinges, blocked tubes, endometriosis, fibroids or prior tubal ectopic pregnancies. Therefore, at first appearance and in absence of additional anatomy-related risk factors, methotrexate intravenously, intramuscularly or into the amnion may be the first choice. In case of anatomical risk factors, cornual wedge resection seems to be first choice. In case of recurrence, cornual wedge resection is particularly justified in patients with anatomical alterations of the salpinges. The role of conservative surgical treatments in recurrence as cornuotomy, salpingectomy, endoloop ligation and resection and curettage under laparoscopic guidance remains unclear due to sparse data.
Keywords: ectopic pregnancy; interstitial pregnancy; angular pregnancy; cornual pregnancy; recurrent ectopic pregnancy